TINJAUAN MINAT BELAJAR PADA MAHASISWA DALAM PELAKSANAAN PEMBELAJARAN DARING DI ERA NEW NORMAL - Saniya Saniya; yulia febrianita; Nur Aulia (LPPM Universitas Abdurrab, 2022)
Abstract Interest is the tendency of the soul towards something consisting of feelings of pleasure, attention, sincerity, the existence of motives and goals in achieving a goal. While learning is related to changes in a person's behavior towards a certain situation caused by repeated experiences in that situation, where the change in behavior cannot be explained or on the basis of a person's innate response tendency, maturity, or momentary circumstances (eg fatigue, stress, etc.) medicine, and so on). The purpose of this study was to describe student interest in learning in the implementation of online learning in the new normal era of covid-19. This research is a quantitative research with a descriptive design. The population in this study were all nursing students from the 2019-2021 class. And the number of samples is 96 students. Based on the results of the study, the majority showed that the lecturers explained the direction and purpose by explaining that most of the students were enthusiastic about learning. This can be seen from the students' answers where as many as 53.7% of students stated always and 25.3% said rarely, based on the data above it is also known that 21.1% of students sometimes 0% of students not at all. Various obstacles found during the online learning process can affect the psychological condition of students, the largest batch is level 1 with a total of 43 respondents (45.3%). So that a solution is needed to overcome these obstacles, for example the ability to manage learning interests is faced. The research shows that there are some students who still have low interest in learning. Keywords : Interest in learning, Online, New normal era